PUTUSAN PENGADILAN NOMOR 37/PDT.G/2021/PN PTK TERKAIT WANPRESTASI KREDIT TERHADAP HAK TANGGUNGAN - Nurhandayani, Nyemas Tania Kintan; Tiara, Niski (Universitas Muhammadiyah Ponorogo, 2024)
The study was conducted with the aim of analyzing the application of mortgage rights in the context of credit default, as reflected in Court Decision Number 37/PDT.G/2021/PN Ptk. This study uses two approaches to analyze Supreme Court Decision Number 37/Pdt.G/2021/PN Ptk, namely document study and normative approach. Document study focuses on the analysis of copies of court decisions and related legal documents to understand the elements of the case and the applicable legal context. The normative approach is used to evaluate the application of appropriate legal principles and norms, as well as to assess the fairness and effectiveness of court decisions. The results of the analysis found that Court Decision Number 37/PDT.G/2021/PN Ptk provides comprehensive handling of credit default cases by prioritizing the evaluation of evidence and the careful application of legal principles. The judge carefully assesses the violation of the agreement by the debtor, including late payments and inadequate reasons, and considers the arguments of the creditor regarding claims for compensation and mortgage rights. The court also uses mortgage rights as an instrument of protection for creditors to ensure compensation for unpaid debts. Even if the debtor submits reasons such as financial inability as a defense, the judge may reject the argument because it is not sufficiently supportive to release the debtor from liability. By referring to the applicable legal provisions, including the Banking Law and mortgage rights, the judge's decision ensures fairness and legal compliance in enforcing collateral obligations.